Efectos de la congestión de las redes de transmisión en la competencia en mercados eléctricos de producción hidrotérmica - E. Luyo, Jaime (2008)
This essay analyzes the network-transmission lines congestion effects on the wholesale generation spot market competence, with a hydrothermal electricity production, and within an oligopolic environment. It develops a Nash-Cournot equilibrium model.